The Mode Expansion of the String Fields (Bulletin of Pure and Applied Sciences – Physics, 2023)
The expansion of the string coordinates is different curved surfaces and space times. A  summation of uniformizing group elements is necessary at genus g ≥ 1. The invariances  are listed for the sigma model action in a maximally curved space-time. Thecritical  dimension is established through conditions on the quantum commutators.